Antipsychotic-Related Risks of Type 2 Diabetes Mellitus in Enrollees With Schizophrenia in the National Basic Public Health Service Program in Hunan Province, China - Ouyang, Feiyun; He, Jun; Cheng, Xunjie; Zhou, Wei; Xiao, Shuiyuan; Fang, Junqun (Frontiers in Psychiatry, 2022)
Background: Antipsychotics contribute to the development of type 2 diabetes mellitus (T2DM) in individuals with schizophrenia. However, the extent of the relationship between antipsychotic use and T2DM varies in different settings, and the magnitude of the drug-specific effects fluctuates widely. This study aimed to explore the association of T2DM with antipsychotic use among enrollees with schizophrenia in China’s National Basic Public Health Service Program (NBPHSP) and the drug-specific relationship with T2DM among patients receiving antipsychotic monotherapy. Methods: We recruited diabetes-free patients with schizophrenia who were enrolled in the NBPHSP of Hunan Province from October 2009 to December 2018. The participants were classified into the following three groups: regular antipsychotic use, intermittent antipsychotic use, and antipsychotic-free groups. The patients were followed up until they received a T2DM diagnosis or until April 2019. Cox regression models were constructed to calculate the overall and drug-specific hazard ratios (HRs) to determine the antipsychotic–T2DM relationship. Interactive and subgroup analyses were performed to assess the heterogeneity of the effects across subgroups. Results: A total of 122,064 NBPHSP enrollees with schizophrenia were followed up for 1,507,829 cumulative person-years, and 2,313 (1.89%) patients developed T2DM. Patients who regularly and intermittently used antipsychotics had 117% (HR: 2.17, 95% CI: 1.83–2.57) and 53% (HR: 1.53, 95% CI: 1.23–1.90) higher risks of developing T2DM than antipsychotic-free patients, respectively. Regarding monotherapy, the T2DM risk increased by 66%, 80%, 62%, and 64% after the regular use of clozapine, risperidone, chlorpromazine, and perphenazine, respectively. In addition, the antipsychotic-related risk of T2DM decreased as the patient’s baseline body mass index, and baseline fasting plasma glucose level, as well as the dietary proportion of animal products, increased. Conclusion: Antipsychotics, especially clozapine, risperidone, chlorpromazine, and perphenazine, increased the T2DM risk among NBPHSP enrollees with schizophrenia. Mental health officers should accurately identify enrollees at a high risk of T2DM and take appropriate preventive measures to reduce the incidence of T2DM among patients with schizophrenia.